Energy landscape modeling of crystal nucleation. (15th September 2021) - Wilkinson, Collin J.; Cassar, Daniel R.; DeCeanne, Anthony V.; Kirchner, Katelyn A.; McKenzie, Matthew E.; Zanotto, Edgar D.; Mauro, John C.
Graphical abstract: Image, graphical abstract Abstract: Nucleation is a crucial phase transformation process across all materials science. In the context of crystal nucleation, accurate knowledge of the nucleation rate is essential for the design of next-generation glass-ceramic and other composite materials; however, the quantitative prediction of crystal nucleation rate versus temperature remains elusive. This work proposes an energy landscape method to account for the thermodynamic and kinetics aspects of nucleation. This energy landscape approach shows fair agreement with experimental nucleation data for the barium disilicate system used as a model. It is also used to gain insight into the fundamental physics of classical nucleation theory (CNT) and a new method to compute nucleation rates.